Estimates of numbers of White sharks (Carcharodon carcharias) in Eastern and Southern South Africa : a post-moratorium assessment - Tress, Mary Elizabeth (Department of Biological Sciences, 2014)
A moratorium was placed on fishing for white sharks (Carcharodon carcharias) in South Africa in 1991 prior to knowing the population status of this species. A mathematical model was developed to estimate the total numbers of white sharks from 1950 to 2050 in the presence of fishing (F = 0.055 year-I) and without fishing (moratorium). The total number of white sharks from Richard's Bay to Struis Bay, South Africa was estimated to be 1,954 (range= 1,855-2,050) for the year 2004. If the moratorium was to be lifted and fishing was to resume, the results of the model indicate that the instantaneous fishing mortality rate F of 0.035 year-l or less allows the population to increase in numbers from 2004 to 2050. A sensitivity analysis determined that the instantaneous natural mortality rate M (tested range=0.070-0.l90 year-I) and the average number of pups per mature pupping female (tested range=4-14 pups) were highly sensitive parameters of the model. The maturity age span (maturity minimum age=13 and 16 years; longevity=23, 36, and 60 years) and timeframe of the female reproductive cycle (two or three years) were the least sensitive parameters of the model.